2011
DOI: 10.1093/abbs/gmq108
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane proteome analysis of the early effect of alcohol on liver: implications for alcoholic liver disease

Abstract: In humans, the over-consumption of alcohol can lead to serious liver disease. To examine the early effects of alcohol on liver disease, rats were given sufficient ethanol to develop liver cirrhosis. Rats before the onset of fibrosis were studied in this work. Plasma membranes (PM) of liver were extracted by twice sucrose density gradient centrifugation. The proteome profiles of PM from ethanol-treated rats and the controls were analyzed using two-dimensional gel electrophoresis (2-DE) and isobaric tag for rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…In addition, p < 0.05 was determined to be significant for protein quantification. Foldchanges of >1.5 or <0.66 were set as cutoff values to designate significant changes in protein expression [20]. The peptide and proteins were exported and saved as txt files.…”
Section: 5mentioning
confidence: 99%
“…In addition, p < 0.05 was determined to be significant for protein quantification. Foldchanges of >1.5 or <0.66 were set as cutoff values to designate significant changes in protein expression [20]. The peptide and proteins were exported and saved as txt files.…”
Section: 5mentioning
confidence: 99%
“…Some proteins were revealed to be related with OS such as pigment epithelium-derived factor [14], small leucine-rich repeat proteoglycans [15], and CD151 [8]. In order to dig out new drug targets or biomarkers, new methods such as subcellular proteome research were adopted to offer new insights [2,8,[16][17][18]. Because most of the drug targets are proteins located in the plasma membrane, we specifically focused our study on the plasma membrane proteome.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that GPS has protective effects on the hepatobiliary system [13][14][15]. In recent years, the mechanisms of chemicals and Chinese herbal medicines in liver diseases [16][17][18][19][20] such as liver fibrosis [21][22][23] have been investigated. In addition, metabolomics has also been used to study the mechanisms of disease by detecting small metabolites produced by normal or pathological cellular processes [24].…”
Section: Introductionmentioning
confidence: 99%